Non-Economic Structure of Consumer Sentiments: The Role of Social Embeddedness in Variability of Consumer Expectations - Pashkov, Stanislav (Journal of Economic Sociology, 2024)
The review is devoted to the discussion around research on consumer expectations, with a focus on the methodological aspects and current problems of measuring the Consumer Sentiment Index (CSI) from a sociological perspective. The need to discuss the role of non-economic factors in the formation of consumer expectations is substantiated by sociological (socio-demographic) foundations, the influence of social environment (institutions), and the entrenched role of mass media. This approach allows us to explain “anomalies” that emerge in time series models, especially during periods of economic turbulence. As part of the study, the history of psychological economics (the theoretical basis of PPI) is provided, and key approaches, theses and studies are considered. Most studies of consumer sentiment before the 1990s were descriptive in nature, based on economic data without deep reflection. Since the 1990s, new directions and studies have emerged, aiming to find meaningful explanation for changes in the index during periods of economic change. However, the findings are often disjointed and fail to establish systematic connections between consumer expectations, social factors and macroeconomics. One option for developing a “middle-range theory” involves constructing a conceptual framework based on the concept of embeddedness proposed by S. Zukin and P. DiMaggio. It has been shown that some forms of embeddedness make it possible to explain deviations and stable trends in the analysis of time series at a meaningful level. In this case, mass media can not only methodically complement the analysis of the CSI, but also plays a role in the rootedness of economic action. An important result of the work is the development of an updated conceptual framework that includes embeddedness as a significant variable in the construction of econometric models, indicating the specifics and possible limitations of this approach. The article contributes to the expansion of the utilization of CSI in sociological longitudinal studies, including the incorporation of mass media as an additional variable.